Penerapan Teori Sistem Dalam Pembelajaran Al-Qur’an Di Sekolah Dasar Islam Terpadu - Shalahudin, Shalahudin; Kusnadi, Edy; Aini, Nur Sarifa (Universitas Pakuan, 2025)
THE IMPLEMENTATION OF SYSTEMS THEORY IN QUR'ANIC LEARNING AT INTEGRATED ISLAMIC ELEMENTARY SCHOOLSThis study aims to analyze the implementation of systems theory in the Qur’an memorization (tahfiz) learning process at the Integrated Islamic Elementary School (SD IT) Al-Qudwah Ujung Jabung. The research focuses on how the principles of systems theory are applied, the supporting and inhibiting factors, and the overall effectiveness of the system in enhancing students' learning outcomes. A qualitative research approach was employed, using observation, in-depth interviews, and document analysis. The results indicate that the tahfiz learning system is well-integrated, involving collaboration between teachers, students, school management, learning facilities, and parental support. Supporting factors include teacher competence, a designated tahfiz room, feedback-based management, and active parental involvement. Main challenges arise from limited study time at school and inconsistent parental assistance at home. Observational data reveal that the learning process occurs in a conducive environment with intensive teacher-student interaction and methods tailored to student characteristics. The system’s effectiveness is reflected in the students’ improved memorization achievements and consistent development of Islamic character. This study concludes that systems theory contributes significantly to sustainable and contextual tahfiz education.